Polypyrrole-Coated Magnetite Vortex Nanoring for Hyperthermia-Boosted Photothermal/Magnetothermal Tumor Ablation Under Photoacoustic/Magnetic Resonance Guidance - Bao, Jianfeng; Guo, Shuangshuang; Zu, Xiangyang; Zhuang, Yuchuan; Fan, Dandan; Zhang, Yong; Shi, Yupeng; Ji, Zhenyu; Cheng, Jingliang; Pang, Xin (Frontiers in Bioengineering and Biotechnology, 2021)
Photothermal/magnetothermal-based hyperthermia cancer therapy techniques have been widely investigated, and associated nanotechnology-assisted treatments have shown promising clinical potentials. However, each method has some limitations, which have impeded extensive applications. For example, the penetration ability of the photothermal is not satisfactory, while the heating efficiency of the magnetothermal is very poor. In this study, a novel magnetite vortex nanoring nanoparticle-coated with polypyrrole (denoted as nanoring Fe3O4@PPy-PEG) was first synthesized and well-characterized. By combining photothermal and magnetothermal effects, the performance of the dual-enhanced hyperthermia was significantly improved, and was thoroughly examined in this study. Benefiting from the magnetite vortex nanoring and polypyrrole, Fe3O4@PPy-PEG showed excellent hyperthermia effects (SAR = 1,648 Wg–1) when simultaneously exposed to the alternating magnetic field (300 kHz, 45 A) and near-infrared (808 nm, 1 W cm–2) laser. What is more, nanoring Fe3O4@PPy-PEG showed a much faster heating rate, which can further augment the antitumor effect by incurring vascular disorder. Besides, Fe3O4@PPy-PEG exhibited a high transverse relaxation rate [60.61 mM–1 S–1 (Fe)] at a very low B0 field (0.35 T) and good photoacoustic effect. We believe that the results obtained herein can significantly promote the development of multifunctional nanoparticle-mediated magnetic and photo induced efficient hyperthermia therapy.